Pengaruh Variasi Pegas CVT dan Massa Roller terhadap Performa Motor 110 cc - Rizki Fatahilah; Purwoko Purwoko; Ratna Monasari; Mira Esculenta Martawati (Jurnal Kendali Teknik dan Sains, 2025)
This study aims to analyze the effect of variations in CVT spring constants (4.94 N/mm, 6.09 N/mm, and 7.38 N/mm) and roller masses (10 g, 13 g, and 15 g) on torque, power, and specific fuel consumption (SFC) of a 110 cc matic motorcycle. Testing was conducted using a dynotest to measure torque and power, and a measuring glass for fuel consumption at engine speeds of 5000–9000 RPM. Results showed a maximum power of 7.93 HP at 7000 RPM with a 10 g roller and 4.94 N/mm spring, the highest torque of 8.56 Nm at 6000 RPM with a 13 g roller and 4.94 N/mm spring, and the lowest SFC of 0.0689 kg/kWh at 9000 RPM with a 10 g roller and 6.09 N/mm spring. Two-Way ANOVA analysis indicated that all factors and their interactions significantly influenced engine performance (p-value < 0.05), with the statistical model showing an R-squared above 97%. The combination of a light roller and medium spring provided the best fuel efficiency, while heavier rollers were more optimal for torque at mid-range RPMs.